Pincer‐Supported Gallium Complexes for the Catalytic Hydroboration of Aldehydes, Ketones and Carbon Dioxide. Issue 69 (27th October 2021) - Liu, Lingyu; Lo, Siu‐Kwan; Smith, Cory; Goicoechea, Jose M.
Abstract: Gallium hydrides stabilised by primary and secondary amines are scarce due to their propensity to eliminate dihydrogen. Consequently, their reactivity has received limited attention. The synthesis of two novel gallium hydride complexes HGa(THF)[ON(H)O] and H2 Ga[μ 2 ‐ON(H)O]Ga[ON(H)O] ([ON(H)O] 2− = N, N ‐bis(3, 5‐di‐ tert ‐butyl‐2‐phenoxy)amine) is described and their reactivity towards aldehydes and ketones is explored. These reactions afford alkoxide‐bridged dimers through 1, 2‐hydrogallation reactions. The gallium hydrides can be regenerated through Ga−O/B−H metathesis from the reaction of such dimers with pinacol borane (HBpin) or 9‐borabicyclo[3.3.1]nonane (9‐BBN). These observations allowed us to target the catalytic reduction of carbonyl substrates (aldehydes, ketones and carbon dioxide) with low catalyst loadings at room temperature. Abstract : The synthesis of two novel gallium hydride complexes supported by an N, N ‐bis(3, 5‐di‐ tert ‐butyl‐2‐phenoxy)amine pincer ligand is described and their activity as catalysts for the catalytic reduction of aldehydes, ketones and carbon dioxide is explored.